The joint properties of a high-chromium Ni-based superalloy made by diffusion brazing: Microstructural evolution, corrosion resistance and mechanical behavior. (January 2019) - Arhami, Farzam; Mirsalehi, Seyyed Ehsan; Sadeghian, Amirhossein; Johar, Mohammad Hossein
Abstract: The phase transformation during diffusion brazing of high chromium Ni-based Inconel 939 superalloy, using a ternary Ni-14.9 Cr-3.7 B (wt.%) interlayer was studied. The microstructural evolution during the bonding process was governed by isothermal solidification, athermal solidification and solid-state precipitation. A single-phase gamma solid solution was the only phase detected in the isothermally solidified zone (ISZ). However, the cooling-induced solidification led to the formation of proeutectic-gamma, Ni-rich boride, Cr-rich boride and eutectic-gamma at the athermally solidified zone (ASZ) which deteriorated the corrosion resistance of the joints. The ASZ width decreased by increasing the bonding time. A reverse relation between the corrosion resistance and the ASZ width was perceived. The complete isothermal solidification, as well as the highest corrosion resistance, were obtained at the bonding time of 90 min. The solid-state precipitation resulted in the formation of Cr-rich boride particles with two blocky and Widmanstatten morphologies in the diffusion affected zone (DAZ). The hardest structure compared to the other microstructural zones belonged to the ASZ in all the bonds. The shear strength of the joints increased in longer bonding times and a reverse relation between the ASZ width and the shear strength was witnessed. The highest shear strength (∼625 MPa) which was approximately 80% of that of the base metal was achieved in the 90-min sample.